Applying enterprise architecture framework into social framework: case study of e-kariah community portal / Naqiuddin Abd Aziz - Abd Aziz, Naqiuddin (2009)
The objective of this research is to explore the importance applying enterprise architecture framework into social architecture, based on case study of E-Kariah Community Portal. In this research, the researcher will define enterprise architecture and social architecture. Then the researcher will identify suitable component from both architecture that deemed appropriate for the case study of E-Kariah Community portal. Then the researcher will apply the solution into the E-Kariah Community Portal. The researcher also will identify issues that take place during the research and suggest solution to the issues arise.